Monopoli Dalam Prespektif Bisnis Syari'ah - Emi Chulaimi (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2013)
Islam come wishing to uphold justice below/under wings of market norm. big Human respect small, strong assist weak, stupid learn from bright, and human being oppose brutality. Ih}tikār in modern economics defied as monopolistic process of and supply of demand commodity as a mean to get certain advantage. Monopolies and pricing can be conducted if situation of marketing price leap highly. It is of course, what more entitled to control pricing and monopolies power on condition that for the kemaslahatan of throng. Monopolistic and pricing basically harm throng, but, both can be gone into effect in a pinch and unstable price. So that, requirement of throng intention can overcome